The Effects of Off-Axis Loading on Fracture Risk in the Human Tibia - Chakravarty, Avery B. (My University, 2016)
The tibia is a frequent site of injury in frontal automotive collisions. The bulk of experimental cadaveric studies on injury tolerance assume load is applied in line with the leg’s long axis, leaving non-standard postures largely uninvestigated. The purpose of this work was to study the effects of non-standard postures on the tibia’s injury tolerance. A pneumatic system was designed to facilitate impact testing. This system allows the user to fire a projectile of variable mass towards a specimen at a range of velocities by varying the supplied air pressure. Impact tests were performed using pairs of isolated cadaveric tibias. Within each pair of specimens, two postures were compared by varying the angle of the bone’s long axis relative to the direction of impact, representing knee extension and corresponding plantarflexion. It was found that the specimens held further from the axial posture sustained injury at lower forces. Two commonly-used Anthropomorphic Test Device legforms were impacted in these non-standard postures. New load limits were proposed for the use of these devices in off-axis impact testing. In order to compare directly with the loads measured by the legforms, it was necessary to measure forces and moments internal to the bone’s long axis. A non-invasive load estimation method was developed and tested using strain measured from the surface of four specimens. The method performed poorly under impact conditions, but may be refined in the future. Quantifying the effect of posture on injury risk in the tibia allows for the refinement of existing injury criteria. Ultimately, this can be used to enhance the design of protective devices to reduce the incidence of tibia fractures in automotive collisions.
Keywords: biomechanics; bone; impact loading; automotive collision; posture; tibia